Cycles of History: China, North Korea and the End of the Korean War - Sheila Miyoshi Jager (Japan Focus)
In 1895, the Chinese scholar Kang Youwei was on his way to Beijing on a Chinese steamer when his ship was abruptly boarded and searched by a party of Japanese soldiers on the North China Sea. "I was enraged when the Japanese came and searched our ship," he later wrote. "If the court had listened to my advice earlier, we would not have to endure such humiliations." But following China's defeat by Japan in the 1894-5 Sino-Japanese War, this was just the sort of humiliation that China was now forced to endure. That war had been fought over influence in Korea and it marked the end of Korea's tributary relationship with China. It was the beginning of China's decline and Japan's ascendancy in East Asian affairs. For the first time since the founding of the Choson dynasty in 1392, China would have little influence over the Korean peninsula.China regained much of its influence over North Korea during the Korean War years (1950-53) when Mao decided to intervene in that conflict once UN forces crossed the 38th parallel north after landing at Inch'on in September 1950, thus saving North Korea from certain defeat (Chinese forces did not leave the peninsula until 1958). Kim Il Sung's ability to play off the communist superpowers during the years of the Sino-Soviet split in the 1960s largely guaranteed his independence once the war had ended. This situation changed after the collapse of the Soviet Union in 1991. As Beijing and Moscow sharply cut their aid and shunned Pyongyang for better relations with Seoul, the North Korean economy went into precipitous decline.4 Russia's abandonment of the "friendship price" system and its demand for hard currency for exports was a major factor in the collapse of the North Korean economy and starvation on a massive scale.This article assesses the China-North Korean relationship from the outbreak of the Korean War to the present.